Conferências nacionais e políticas públicas para grupos minoritários - Thamy Pogrebinschi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Democratic innovations such as the national public policy conferences have been proving themselves to contribute to the inclusion of historically underrepresented groups in Brazil. That would be particularly true regarding culturally-defined minority groups, such as those whose identity is shaped by gender, racial or sexual issues, as well as other shared ways of life that impose demands for special policies, such as people with disabilities and senior citizens. This article aims to argue that the political representation of minority groups in the Executive and Legislative branches has been enforced by the national public policy conferences, yielding a more inclusive lawmaking and policymaking.
Keywords: Z18; 330; national conferences; inclusion; minority groups; political representation